Oderwany fragment części haptycznej wszczepu soczewkowego przyczyną keratopatii pęcherzowej. Opis przypadku - Jurowski, Piotr (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Presentation of the case of the patient in whom1 year after penetrating keratoplasty a broken, free moving haptic part of the IOL within anterior chamber was found. In accordance to increases of pain and high likelihood of donor corneal flap damage decision about surgical removal of free haptic was undertaken. Finding of the broken part of IOL throw light on the cause of bullous keratopathy in this case.